Assessment of Adherence to Lifestyle Modification Plans and Medications Among Patients with Cardio Metabolic Diseases in Cape Coast Teaching Hospital - Gordon, E. (University of Ghana, 2024)
Background: Cardiovascular diseases (CVDs) are a leading cause of morbidity and mortality globally. In Ghana, limited data on lifestyle changes and treatment adherence among CVD patients hinders effective intervention, with only 5% achieving blood pressure control. Aim: To assess adherence to lifestyle modifications (diet, exercise, alcohol/smoking cessation, stress management) and medication among CVD patients. Method: A convergent mixed-methods research design was used. The study gathered data from a diverse sample of 419 CVD patients at Cape Coast Teaching Hospital. Quantitative surveys collected demographic, medical, and adherence information, while qualitative insights were derived from 15 in-depth interviews and one focus group discussion. Results: Most participants avoided smoking (98.8%) and alcohol (70%) and exercised regularly (66.8%). However, only 28.4% restricted salt, 8.3% controlled glucose, and 5.5% maintained blood pressure. Knowledge of hypertension was low (27%), though medication adherence was relatively high (70%). Major challenges included financial constraints (66.4%) and limited knowledge (46.3%). Comorbidity was associated with lower odds of medication adherence (OR = 0.54, 95% CI: 0.35–0.85, p = .007) and normal fasting glucose (OR = 0.45, 95% CI: 0.21–0.99, p = .047). Increasing age was linked to a higher likelihood of uncontrolled blood pressure (OR = 1.75, 95% CI: 1.22–2.51, p = .002). Integrated findings showed high medication adherence but limited adoption of full lifestyle modification. While most patients practiced healthy behaviors, adherence to salt restriction and structured exercise remained low. Financial hardship, cultural dietary habits, and limited counseling constrained sustained change. Education and provider engagement emerged as facilitators, yet health system resource gaps persisted. Comorbidity, older age, and longer disease duration predicted poorer adherence and clinical control. Overall, meta-inference indicated that motivation alone is insufficient; sustainable adherence requires culturally tailored and system-supported interventions. Conclusion: These findings highlight the need for personalized, comprehensive interventions addressing financial, motivational, and educational barriers to improve adherence and health outcomes in CVD management.
MPH.
Keywords: Cardiovascular diseases (CVDs); morbidity; mortality; Ghana